Leaf Spots and Leaf Blights of Palm - Monica L. Elliott (EDIS)
This fact sheet is limited to those diseases where the pathogens only infect (invade) and cause spots and blights of the leaf blade. Other diseases may cause death of leaflets and leaf segments but are actually the result of a pathogen infecting the leaf petiole or rachis. Petiole/rachis blight diseases are discussed separately at http://edis.ifas.ufl.edu/pp145. This document is PP-218, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date Janurary 2006.